1981
DOI: 10.1007/bf01440915
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of100Tc from100Mo(p,nγ)100Tc reaction and the parabolic rule

Abstract: 7-spectra and excitation functions of the ~~176 nT) l~176 reaction were measured in the 1.2-3.6MeV proton energy range by using thick, enriched targets, Ge(Li) and low energy photon (hyperpure Ge) spectrometers. These detectors were used in YTcoincidence experiments, too. Conversion electron spectrum measurements were performed by means of a superconducting magnet transporter Si(Li) spectrometer (SMS) at Ep =4MeV and multipolarities of some transitions have been determined. Based on the experimental results a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There were several studies which aimed at establishing low-lying levels in 100 Tc using 99 Tc(n th ; ), 22,24) 100 Mo(d; 2n), 24) 99 Tc(d; p), 27) 100 Mo(p; n), [28][29][30] and 96 Zr( 7 Li; 3n) 31 29) investigated low-lying levels of 100 Tc with the same reaction in the energy range of 4:0 E p 6:8 MeV by means ofcoincidence technique, and constructed a level scheme up to 521.0 keV. Á rvay et al 30) reported a level scheme up to 906.1 keV energy.…”
Section: Level Schemementioning
confidence: 99%
See 1 more Smart Citation
“…There were several studies which aimed at establishing low-lying levels in 100 Tc using 99 Tc(n th ; ), 22,24) 100 Mo(d; 2n), 24) 99 Tc(d; p), 27) 100 Mo(p; n), [28][29][30] and 96 Zr( 7 Li; 3n) 31 29) investigated low-lying levels of 100 Tc with the same reaction in the energy range of 4:0 E p 6:8 MeV by means ofcoincidence technique, and constructed a level scheme up to 521.0 keV. Á rvay et al 30) reported a level scheme up to 906.1 keV energy.…”
Section: Level Schemementioning
confidence: 99%
“…Our summary is independent of a similar summary appearing in the Nuclear Data Sheets. 32) The 100 Mo(p; n) 100 Tc studies by Á rvay et al 30) and Bini et al 29) are the backbone of the skeleton level scheme.…”
Section: Level Schemementioning
confidence: 99%
“…32) The 100 Mo(p; n) 100 Tc studies by Á rvay et al 30) and Bini et al 29) are the backbone of the skeleton level scheme.…”
Section: Level Schemementioning
confidence: 99%
“…The ICCs of the transitions in 100 Tc have been measured and reported for some lower shells by several authors. 24,30,31) In order to deduce the capture cross section, however, total ICCs were in need, and therefore, these were calculated theoretically using the reported ICCs to the lower shells in the following manner. At first, for each study which reports ICC values, the reported value was compared to the theoretical value based on Ref.…”
Section: ð1 þ T ðIþþ â I ðIþ; ð1þmentioning
confidence: 99%